PENINGKATAN HASIL BELAJAR PPKn MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI SISWA KELAS IV SD NEGERI 011 BERINGIN MAKMUR KECAMATAN KERUMUTAN - Ambari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
At SD Negeri 011 Beringin Makmur, particularly in Grade IV, the minimum mastery criterion (KKM) for Civics (PPKn) is set at 65. However, students’ PPKn learning outcomes were relatively low, as indicated by the midterm test results showing an average score of only 61.5. Based on the preliminary study conducted by the researcher, the low learning outcomes in PPKn were caused by several factors, including the use of teaching strategies that were not aligned with learning demands and the dominance of lecture-based instruction, which resulted in minimal student participation and questioning during PPKn lessons. Therefore, this study aimed to improve students’ PPKn learning outcomes through the implementation of the inquiry learning model among fourth-grade students at SD Negeri 011 Beringin Makmur. This research employed a classroom action research design conducted through the stages of planning, action implementation, observation, and reflection, using a cyclical model of continuous improvement. The subjects of the study were 30 fourth-grade students at SD Negeri 011 Beringin Makmur, consisting of 15 male and 15 female students. The object of the research was students’ PPKn learning outcomes, and the data collected focused solely on learning outcome data. The results of the actions taken demonstrate a significant improvement in students’ learning outcomes. Based on the preliminary data, only 15 students (50%) achieved mastery learning. After the implementation of actions in Cycle I, the number of students achieving mastery increased to 26 students (87%). Furthermore, following improvements in Cycle II, learning mastery increased to 27 students (90%). These findings indicate that the inquiry learning model is effective in improving PPKn learning outcomes among fourth-grade students at SD Negeri 011 Beringin Makmur.